ANALISIS DERIVATIF DATA GRAVITASI UNTUK MENGIDENTIFIKASI SESAR PADA LAPANGAN GEOTHERMAL âWILLâ - , SURYA AJI SAPUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Study use gravity method has been conducted in the \"WILL\" geothermal field to model the subsurface conditions of the study area. The model then used to determine the geothermal system in the area. Result of preliminary processing of gravity data is Complete Bouguer Anomaly data which then filltering by upward continuation to separate regional and residual anomaly. Residual anomalies data are then processed with derivative analysis such as First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) to identify rock structure and other possibilities. Seven 2D model was made from residual anomalies data and correlated with FHD, SVD, and geological data. There is 4 rock formation identified from the models, each with unique density value, which is Waringin Formation (2,55 gr/cm3) such as reservoir, Pangalengan Formation (2,30 gr/cm3) such as cap rock, Malabar Formation (2,50 gr/cm3), Wayang-Windhu Formation (2,50 gr/cm3), and Alluvium (1,80 gr/cm3).